The School as an Influencing Factor of Truancy (International Journal of Criminology and Sociology, 2016)
As previous research has shown, truants have a higher risk of becoming delinquent. However, the causes of truancy are only seldom analyzed in criminological research. Since truancy is a school related behavior, it can be assumed that school factors play a major role in causing it. Using a German wide representative sample of almost 40,000 pupils of the ninth grade (mean age: 15 years; 50.3 percent male) from 1,200 schools several school factors and their relationship with truancy are tested. These factors are theoretical derived from a push-and-pull-model. Push factors are for instance teacher bullying or violent schoolmates, pull factors are responsive teachers and positive relationships with schoolmates. The results show that teacher bullying and low teacher control significantly increase truancy. Compared with individual risk factors like self-control or school achievement school factors are of lower importance. Additional analyses reveal that there are interaction effects between individual and school level variables: A high level of teacher bullying particularly increases truancy of pupils with bad grades.